Philosophy of Law in the Old Vilnius University - Plečkaitis, Romanas (Problemos, 2001)
The texts in the philosophy of law written at the old Vilnius University represent the first period in the development of law in Lithuania. The literature of this period was created by the influence of the late scholastic. The following problems of the philosophy of law were discussed: an origin and a foundation of law, a transmission of the legislation, the law as the mean of realization the Christian justice, the theory of statute, the branches of law. The Renaissance philosophy of law in Lithuania criticized the reality of Polish-Lithuanian state, urged to extend the public freedoms, the limits and a content of a civil law.